Electrical energy storage using compressed gas in depleted hydraulically fractured wells - David L. Young (Elsevier, 2021)
Summary: Renewable forms of electricity generation like solar and wind require low-cost energy storage solutions to meet climate change deployment goals. Here, we explore the use of depleted hydraulically fractured (“fracked”) oil and gas wells to store electrical energy in the form of compressed natural gas to be released to spin an expander/generator when electrical demand is high. Our reservoir model indicates that the same dual-porosity geological environment of fracked wells used to liberate hydrocarbons is also suitable for storing and releasing gas in a diurnal or seasonal cycle. Round-trip storage efficiency is calculated to be 40%–70% depending on the natural reservoir temperature. Levelized cost of storage is estimated to be $70–270/MWh, on par with pumped hydro storage. This study indicates that repurposed “fracked” wells could provide a much-needed low-cost seasonal energy storage solution at the TWh scale.